2008
DOI: 10.1002/nau.20492
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and body composition analysis of nocturia in the elderly

Abstract: These results suggest that sleep disturbance, hypertension, and excessive fluid intake are major factors contributing to an increased frequency of nocturnal urination (>twice per night) in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 44 publications
(51 reference statements)
3
61
1
Order By: Relevance
“…Elderly patients with nocturia have been reported to have high levels of HANP and/or BNP (19,22). However, in the present study, the baseline level of HANP before exercise was within the normal range although its level was slightly decreased after exercise.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Elderly patients with nocturia have been reported to have high levels of HANP and/or BNP (19,22). However, in the present study, the baseline level of HANP before exercise was within the normal range although its level was slightly decreased after exercise.…”
Section: Discussioncontrasting
confidence: 82%
“…According to our previous study, an increase of serum catecholamine levels was one of the characteristics of elderly persons with nocturia (19). Recently, it has been suggested that the occurrence of nocturia can be attributed to nocturnal polyuria and/ or diminished nocturnal bladder capacity (11,23), diastolic blood pressures, body weight, body fat ratio, edema ratio, serum catecholamines, TG, and T-Chol in this study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been reported that HTN can increase the risk of nocturia by two folds, and the presence of these two conditions can simultaneously effect quality of life (45). Similar findings have been reported from elsewhere (46,47). In addition, a dose-response relationship for all age groups was found between HTN and nocturia with stronger association during old age (48).…”
Section: Discussionsupporting
confidence: 68%
“…typical cause of nocturia, and the plasma melatonin level of patients with nocturia is significantly lower than that of those without nocturia [14]. Hypnotics including zolpidem reduce the frequency of nocturia to about once nightly [8,12,15], and the effect of melatonin on nocturia has been reported to be similar to that of hypnotics [8].…”
Section: Resultsmentioning
confidence: 98%